2015
DOI: 10.1007/s11517-015-1276-9
|View full text |Cite
|
Sign up to set email alerts
|

Upper-limb kinematic reconstruction during stroke robot-aided therapy

Abstract: The paper proposes a novel method for an accurate and unobtrusive reconstruction of the upper-limb kinematics of stroke patients during robot-aided rehabilitation tasks with end-effector machines. The method is based on a robust analytic procedure for inverse kinematics that simply uses, in addition to hand pose data provided by the robot, upper arm acceleration measurements for computing a constraint on elbow position; it is exploited for task space augmentation. The proposed method can enable in-depth compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…Many stroke survivors (about 42 million in 2015) ( Vos et al, 2016 ) sustain neurological damage, which is often permanent. Among other impairments, stroke can compromise use of the upper limbs, thereby negatively impacting common daily living activities (ADL) ( Papaleo et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many stroke survivors (about 42 million in 2015) ( Vos et al, 2016 ) sustain neurological damage, which is often permanent. Among other impairments, stroke can compromise use of the upper limbs, thereby negatively impacting common daily living activities (ADL) ( Papaleo et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…That is because this type of devices are able to record kinematic and kinetic data. From this data, useful markers can be extracted to quantify the motor recovery process during the therapy (Volpe et al, 2009; Einav et al, 2011; Bertomeu-Motos et al, 2015; Papaleo et al, 2015). Recently in Norouzi-Gheidari et al (2012), it is shown that the rehabilitation sessions performed with the robotic device get better recovery outcomes than the conventional therapy during the rehabilitation of the upper limb of stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Mihelj developed a method to estimate the arm joints through two accelerometers placed onto the upper arm [ 9 ]. Then, Papaleo et al improved this method using a numerical integration through the augmented Jacobian in order to estimate the arm configuration with only one accelerometer [ 10 , 11 ]. This algorithm performs a kinematic reconstruction of the simplified human arm model with seven degrees of freedom (DoFs) assuming that the shoulder is fixed during the therapy.…”
Section: Introductionmentioning
confidence: 99%